Effect of Carbon, Nitrogen Sources and Water Activity on Growth and Ochratoxin Production of Aspergillus carbonarius (Bainier) Thom - Hashem, Abeer (Jundishapur J Microbiol, 2015)
BACKGROUND: Ochratoxin A (OTA) is a toxic secondary metabolite produced by fungi belonging to Aspergillus and Penicillium genera. The production of OTA is influenced by environmental conditions and nutritional requirements. The postharvest application of bunches of table grape fruit (TGF), with water activity of 0.8 a(w), was highly effective for controlling OTA contamination in vitro and in vivo (table grape). OBJECTIVES: The aim of this study was to determine the influence of environmental conditions and nutritional requirements on growth and OTA production by Aspergillus carbonarius, as well as, the impact of water activity on OTA production and growth characters of A. carbonarius. Furthermore, we also examined the influence of the application of different levels of water activity (a(w) 0.8) on the preservation of the general appearance of TGF and control of their contamination with OTA. MATERIALS AND METHODS: The growth and OTA production by A. carbonarius were studied using glucose-ammonium nitrate salt broth medium. Effect of water activity was studied using glycerol (0.80, 0.85, 0.90, and 0.98 a(w)). The bunches of table grape fruits were immersed in glycerol solution (equivalent to 0.80 a(w)) and placed as a double layer in cardboard boxes (25 × 35 × 10 cm). The boxes were stored at 20°C for 15 days to simulate local market conditions. RESULTS: The maximum OTA production by A. carbonarius was observed on broth medium after eight days of incubation at 20°C, with pH 4, and fructose and ammonium nitrate supplementation as carbon and nitrogen sources, respectively. The water activity (0.9, 0.85 a(w)) caused significant decrease in OTA production by A. carbonarius. The postharvest application of water activity (0.8 a(w)) was highly effective for maintenance of the table grape quality, which was expressed as weight loss, firmness and decay, while it also controlled OTA contamination of fruits under concept of local market conditions. CONCLUSIONS: Our results reported that deterioration of TGF by A. carbonarius could be minimized by application of a(w). Our experiments were performed under conditions of local markets, which support the economy of many thousands of families in Egypt, especially in the poor rural areas. In future adequate research is required to use these technologies commercially.